2020
DOI: 10.1016/j.jmoldx.2020.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive and Specific Detection and Serotyping of Five Prevalent Salmonella Serovars by Multiple Cross-Displacement Amplification

Abstract: Salmonella is a common cause of foodborne disease worldwide, including Australia. More than 85% of outbreaks of human salmonellosis in Australia were caused by five Salmonella serovars. Rapid, accurate, and sensitive identification of Salmonella serovars is vital for diagnosis and public health surveillance. Recently, an isothermal amplification technique, termed multiple cross-displacement amplification (MCDA), has been employed to detect Salmonella at the species level. Herein, seven MCDA assays were develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Previous reports have demonstrated that MCDA-based methods were 10-fold to 1000-fold more sensitive than PCR assays, even at least 10-fold more sensitive than the most popular LAMP assay. 17 The data of analytical sensitivity suggested that COVID-19 MCCD was able to detect down to seven copies (of each target gene) per test ( Figure 3 ). The results obtained using an LFB were in complete agreement with the fluorescence readout ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have demonstrated that MCDA-based methods were 10-fold to 1000-fold more sensitive than PCR assays, even at least 10-fold more sensitive than the most popular LAMP assay. 17 The data of analytical sensitivity suggested that COVID-19 MCCD was able to detect down to seven copies (of each target gene) per test ( Figure 3 ). The results obtained using an LFB were in complete agreement with the fluorescence readout ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…For MCDA, this is the first study to directly benchmark the speed and sensitivity of MCDA to RT-PCR against the same targets. Previous MCDA studies only compared gel-based PCR 4 , different RT-PCR gene targets 15,16 or used RT-PCR sensitivity results previously reported in other studies (as 100 copies in different studies may not be equivalent) 4,5 . In order to benchmark different nucleic acid techniques, we used and recommend the same reaction volume, same machine, same DNA standards and aliquots, and where possible the same run is used.…”
Section: Discussionmentioning
confidence: 99%
“…For each region, 4 sets of MCDA primers were designed as previously described 5 . Each primer set consisted of 2 cross-primers (CP1/CP2), 2 displacement primers (F1/F2) and 6 amplification primers (C1/C2, D1/D2, R1/R2) (Supplementary Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other tests developed include serological assays that rely on IgM/IgG antibodies which takes ~ 5 days to appear after symptom onset making them unsuitable for rapid early detection 2 .The development of alternative nucleic acid amplification methods including loop-mediated isothermal amplification (LAMP) may offer improved speed, sensitivity and portability for SARS-CoV-2 detection 3 . Another isothermal nucleic acid amplification method, called multiple cross displacement amplification (MCDA) which uses 10 primers instead of six, has also been suggested to have even higher sensitivity and speed than LAMP but has not yet been developed for SARS-CoV-2 detection 4,5 .Despite claims of increased speed and sensitivity from isothermal amplification methods, no study has directly compared the speed and sensitivity of these three different nucleic acid amplification methods. Hence, here we developed an MCDA assay for SARS-CoV-2 detection and compared its speed and sensitivity to existing LAMP and rt-PCR methods.…”
mentioning
confidence: 99%